Effect of Eriodictyol on Collagen-Induced Arthritis in Rats by Akt/HIF-1α Pathway - Lei Z; Ouyang L; Gong Y; Wang Z; Yu B (Dove Medical Press, 2020)
ZhongHua Lei,1,2,* Liu Ouyang,3,* Yong Gong,1 ZhaoZhen Wang,1 Bo Yu1 1Department of Orthopedics, Zhujiang Hospital, Southern Medical University, Guangzhou 510282, People’s Republic of China; 2Department of Orthopedics, The Sixth Peoples Hospital of Huizhou, Huizhou 516211, People’s Republic of China; 3Department of Orthopedics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo Yu Email yubozj@yeah.netPurpose: The aim of the experiment was to explore the effect of eriodictyol (ERI) on arthritis.Methods: We established a rat model of collagen-induced rheumatoid arthritis (CIA) using type II collagen plus Freund’s complete adjuvant. We evaluated the degree of paw swelling, joint pathology, inflammatory cytokine levels, and the Akt/hypoxia-inducible factor (HIF)-1α signaling pathway in the CIA rats.Results: ERI significantly ameliorated joint swelling; improved joint pathology; and suppressed the release of interleukin-6, interleukin-1 beta, and tumor necrosis factor-alpha. Moreover, ERI inhibited the Akt/HIF-1α pathway in the joints of rats and in lipopolysaccharide-treated RAW264.7 cells.Conclusion: ERI ameliorated arthritis in a manner involving the Akt/HIF-1α signaling pathway.Keywords: Eriodictyol, arthritis, inflammation, Akt/HIF-1α pathway